Effect of Local Culture-based Nutrition Education on Compliance with Iron and Folic Acid Supplementation in Female Adolescent - Rahmiwati, Anita; Djokosujono, Kusharisupeni; Krianto, Tri; Utari, Diah Mulyawati; Djuwita, Ratna; Setiarini, Asih; Besral, Besral; Purnama, Dadang Hikmah; Dwiriani, Cesilia Meti; Mulyana, Nana (UI Scholars Hub, 2023)
The non-compliance of female adolescents with the consumption of iron and folic acid supplementation (IFAS) poses a challenge to reducing the incidence of anemia. Therefore, this study aimed to determine the effect of nutrition education using the local culture-based approach on the level of knowledge and attitudes regarding awareness, interest, evaluation, trial, and adoption dimensions, as well as compliance of female adolescents in consuming IFAS. The intervention was conducted using a quantitative quasi-experimental design approach. The sample comprised 68 and 58 senior high school girls in the control and intervention groups. The intervention group received IFAS and local culture-based nutrition education for 12 weeks and followed up after four weeks; while, the control group was given a leaflet and IFAS. Univariate analysis was conducted to analyze the participants’ characteristics; while, bivariate analysis used an independent T-test. The multivariate analysis was carried out using multiple linear and logistic regression analyses. The study showed a statistically significant increase in knowledge and attitudes scores in the intervention group (p-value<0.01) compared to the control group. In conclusion, the compliance with IFAS in the intervention group was 82.8%.